Pedestrian detection using Doppler radar and LSTM neural network - Mussyazwann Azizi Mustafa Azizi; Mohammad Nazrin Mohd Noh; Idnin Pasya; Ahmad Ihsan Mohd Yassin; Megat Syahirul Amin Megat Ali (IAES International Journal of Artificial Intelligence (IJ-AI), 2020)
Integration of radar systems as primary sensor with deep learning algorithms in driver assist systems is still limited. Its implementation would greatly help in continuous monitoring of visual blind spots from incoming pedestrians. Hence, this study proposes a single-input single-output based Doppler radar and long short-term memory (LSTM) neural network for pedestrian detection. The radar is placed in monostatic configuration at an angle of 45 degree from line of sight. Continuous wave with frequency of 1.9 GHz are continuously transmitted from the antenna. The returning signal from the approaching subjects is characterized by the branching peaks higher than the transmitted frequency. A total of 1108 spectrum traces with Doppler shifts characteristics is acquired from eight volunteers. Another 1108 spectrum traces without Doppler shifts are used for control purposes. The traces are then fed to LSTM neural network for training, validation and testing. Generally, the proposed method was able to detect pedestrian with 88.9% accuracy for training and 87.3% accuracy for testing.